CONCEPTUALISING KNOWLEDGE SOCIETY IN A POSTHUMAN WORLD: A Study of Rudy Rucker’s Postsingular - Jose, Anita (Journal of Dharma, 2019)
The notion of the posthuman is often received with apprehensions and anxiety surrounding an apocalyptic future that awaits humanity. Even as popular versions of the term exhibit inclination towards such a possibility, philosophical ruminations of posthumanism offer an optimistic outlook regarding an ideal future. The article traces the ramifications of a technologically singular world and its implications in the creation of a knowledge society in a posthuman world, weighing considerations that constitute transhumanist and posthumanist environments that populate the universe of the novel Postsingular by Rudy Rucker. The destructive tendencies inherent in the advent of singularity need not be eradicated by evincing a transition towards a postsingular environment, but may be rectified by altering the human intentions that favour possessive individualism and human exceptionalism. The paper seeks to foreground the philosophical implications embedded in the term posthumanism that works to dismantle an anthropocentric framework to embrace an egalitarian outlook which contains all beings in its fold irrespective of speciestic boundaries and thereby examine the renewed notions with respect to knowledge sharing, global networking and digital singularity that considers the significance of these concepts beyond the realm of the human.